The biological activity assessment of potential drugs acting on cardiovascular system using Lipinski and Veber Rules - Kowalska, Magdalena; Fijałkowski, Łukasz; Nowaczyk, Alicja (Journal of Education, Health and Sport, 2018)
Advanced computational methods (in silico) play major role in the early stages of developing new pharmaceuticals. Precise knowledge on molecular structure gives the possibility of forecasting the drug candidates basic properties. Despite many drugs registered in the arrhythmia treatment, this disease currently is still a big therapeutic problem. Therefore, intensive search for new drugs acting on the cardiovascular system are performed.In the presented work, 77 pyrrolidin-2-one derivatives were analyzed for antiarrhythmic activity. Values of the key parameters proposed by Lipinski and Veber were obtained using computational chemistry methods. It's worth pointing out that the studied group of derivatives shows similar physicochemical properties to the anti-arrhythmic drugs used.